STRATEGI PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM CUILAN ZENK DI DESA GODEAN KABUPATEN NGANJUK - Rizki, Vina; Isbandono, Prasetyo (Universitas Negeri Surabaya, 2023)
Community Empowerment Through the Cuilan Zenk MSME Program in Godean Village, Nganjuk Regency. Implementation of participatory development is a form of creative innovation for the residents of Godean Village, from zinc chips to household products that have economic value. Community empowerment still needs to run optimally given to Cuilan Zenk MSME actors and is a form of tourism centre. He managed culinary to increase economic growth. This research aims to describe community empowerment strategies through the Cuilan Zenk MSME program. The research method used was Milles and Huberman's analysis. The research results show community empowerment through the Cuilan Zenk MSME program is going well with the first indicator, Motivation. The Godean Village Government often appeals to develop the potential of the Cuilan Zenk Program so that it is managed well. Providing advice and Motivation is carried out both officially and personally to traders who participate in the scope of business actors in the Cuilan Zenk program. Second, the Skills Training program for the Cuilan Zenk MSME empowerment program has been implemented. Socialization and training activities are more about soft skills training in collaboration with the Nganjuk Regency Industry and Trade Service. Third, the self-management of business actors in Cuilan Zenk began to grow after socialization and activity carried out by various parties from both the Godean Village Government Service and the Nganjuk Regency regional government with evidence from the increase in traders in the Cuilan Zenk program to 18 business units, and now there are 24 business units. Fourth, resource mobilization in the Cuilan Zenk MSME empowerment program has been accommodated quite well. Each business unit still relies on personal capital with assistance from anywhere for each business unit. Keywords: Empowerment, Cuilan Zenk, Godean Village